2022
DOI: 10.1039/d2dt00838f
|View full text |Cite
|
Sign up to set email alerts
|

Combined experimental and theoretical investigation on the magnetic properties derived from the coordination of 6-methyl-2-oxonicotinate to 3d-metal ions

Abstract: Five new compounds are reported herein starting from 2-hydroxy-6-methylnicotinic acid (H2h6mnic) and first-row transition metal ions, although H2h6mnic shows a prototropy in solution to lead to the 6-methyl-2-oxonicotinate (6m2onic) ligand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
2
2
0
Order By: Relevance
“…On the other hand, the second centre shows a (dz 2 ) 2 (dx 2 − y 2 ) 2 (dyz) 1 (dxy) 1 (dxz) 1 configuration, which reproduces more faithfully the energy order found in tetrahedral environments, except for the fact that orbital degeneracy is also broken in the present case. With regard to the magnetic anisotropy, the calculations give opposite signs for the values of the axial parameters as well as non-negligible rhombic contributions, which are consistent with other previously published works ( D = −41.1 cm −1 and E / D = 0.20 for TPR, D = 24.0 cm −1 and E / D = 0.25 for Td environments) [ 34 , 35 , 36 ]. The major contributions to these parameters come from the ground-to-first and ground-to-second excited states, among which the origin of the rhombicity derives from the second and first excitations, respectively, for the distorted TPR and Td environments.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, the second centre shows a (dz 2 ) 2 (dx 2 − y 2 ) 2 (dyz) 1 (dxy) 1 (dxz) 1 configuration, which reproduces more faithfully the energy order found in tetrahedral environments, except for the fact that orbital degeneracy is also broken in the present case. With regard to the magnetic anisotropy, the calculations give opposite signs for the values of the axial parameters as well as non-negligible rhombic contributions, which are consistent with other previously published works ( D = −41.1 cm −1 and E / D = 0.20 for TPR, D = 24.0 cm −1 and E / D = 0.25 for Td environments) [ 34 , 35 , 36 ]. The major contributions to these parameters come from the ground-to-first and ground-to-second excited states, among which the origin of the rhombicity derives from the second and first excitations, respectively, for the distorted TPR and Td environments.…”
Section: Resultssupporting
confidence: 90%
“…It is worth noticing the fact that the latter undergoes a prototropy that involves the migration of the hydroxyl hydrogen atom to the pyridinic nitrogen, which results in an N-H group that yields the 6-methyl-2-oxonicotinate ligand (6m2onic). This equilibrium has been previously observed for other previously published compounds based on this ligand, 49,50 and it seems to be pushed by the formation of a six-membered chelating ring with the metal ion formed by the ketone and adjacent carboxylate oxygen atoms, a structural feature that defines the coordination environment of the present compounds. In this sense, it has been observed that the free ligand itself undergoes the prototropic reaction in water solution since H6m2onic is the final crystallization product when H2h6mnic is dissolved.…”
Section: Resultssupporting
confidence: 82%
“…49 This result must be attributed to the hydrogen bonding interactions occurring in the crystal structure of H6m2onic because, as confirmed in our previous work in which both ligands have been optimized at DFT level, H2h6mnic tautomer is indeed the most stable molecule. 50 On the other hand, it is also worth mentioning that the compound requires the addition of sodium hydroxide not only for the presence of sodium cation in the medium but also for meeting a more basic solution that favours the deprotonation of the ligand (see Scheme 1). The synthesised CPs are isostructural, as revealed by the analysis of the X-ray diffraction data, and crystallize in the Pbca space group in the form of one-dimensional arrays.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of basis set can be important for the exchange coupling calculation. Selecting a fairly large basis set for paramagnetic metal ions while keeping reasonable ones for the other atoms is frequently recommended [ 69 , 98 , 99 ]. This has been shown to work well for systems without radical ligands.…”
Section: Resultsmentioning
confidence: 99%